21st birthday - Patterson, James, 1947-; Paetro, Maxine (New York : Little Brown and Company, 2021)
"SFPD Sergeant Lindsay Boxer has sworn to defend against all enemies, foreign and domestic. As Lindsay prepares to celebrate her own daughter's birthday, she clashes with rising Chief Charlie Clapper over a family case."--
Keywords: Missing persons -- Fiction; Murder -- Fiction; Detective and mystery fiction; Thrillers (Fiction)